ANALISIS FAKTOR INTERNAL HARGA SAHAM PERUSAHAAN HOTEL, RESTORAN, DAN PARIWISATA DI BURSA EFEK INDONESIA - Meisya Najunda Putri (2021)
Quantitative research with the aim of knowing the effect of Leverage, Profitability, and Market Value on Stock Prices. Where the population used is hotel, restaurant, and tourism companies listed on the Indonesia Stock Exchange (IDX). Sample selection using non-probability sampling method with saturated samples, there are 41 hotel, restaurant, and tourism companies. Hypothesis testing using panel data regression analysis method with Eviews 11.0 program and a significance level of 5% (0.05). This study shows the results that Leverage measured by Debt to Equity (DER) has no effect on Stock Prices, Profitability is measured by Return on Equity (ROE) has a positive effect on Stock Prices, and Market Value is measured by Price Earnings Ratio (PER) has no effect on Prices. Share. Keywords: leverage, profitability, market value, and stock price.